Integrated Design Theory And Flight Performance Analysis Of A Surface-Launched Rocket - Saeedjpour, Hamid Reza; Mohd Yusof, lIIyia; Basuno, Bambang (2004)
This paper is outlined the conceptual design and general aspects of flight performance of an advanced Surface-Launched Rocket. Brief descriptions of the technologies in the rocket design, parameters driving the rocket design and performance, the rocket performance prediction and examples of maximizing flight performance are presented.